THE DETERMINANTS OF CERVICAL CANCER EARLY DETECTION BEHAVIOUR WITH VIA TEST METHOD IN VISITORS OF POLI KIA-KB IN KASSI-KASSI PUBLIC HEALTH CENTER OF KOTA MAKASSAR - Ummul Qura; Jumriani Ansar; Dian Sidik Arsyad; Indra Dwinata; Muh Ikhsan; Suriah Suriah (Epidemiology and Society Health Review (ESHR), 2019)
Background: Cervical cancer can be recognized at the pre-cancer stage by doing early detection test in married women. One of the cervical cancer early detection methods is Visual Inspection with Acetic Acid (VIA) test. The coverage of the early detection of cervical cancer through VIA test method in 2017 was still very low, i. e. 1.03% from the national target of 50%. The research aims to know the determinants of cervical cancer early detection behaviour by using IVA test method in visitors of Policlinic KIA-KB (Pediatric and Family Planning Polyclinic) in Kassi-Kassi Public Health Center.Methods: The research was observational analytical research with cross-sectional study design. The population of the study was all women of fertile couple that visited Policlinic KIA-KB in Kassi-Kassi Public Health Center and lived within the coverage area of Kassi-Kassi Public Health Center, which amounted to 135 women. The samples were 101 women that were collected by using the accidental sampling technique.Results: The results showed that there was a relation between knowledge (p=0.000), attitude (p=0.005), husband support (p=0.000), as well as health worker support (p=0.000) and early detection behaviour by using IVA test method. Conclusions: Meanwhile, there was no relation between education and early detection behaviour by using IVA test method. There should be proactive and creative actions from health workers in improving the knowledge of the targets and their husbands about early detection of cervical cancer.